2006
DOI: 10.1002/neu.20257
|View full text |Cite
|
Sign up to set email alerts
|

Metalloprotease‐induced ectodomain shedding of neural cell adhesion molecule (NCAM)

Abstract: Transmembrane forms of neural cell adhesion molecule (NCAM140, NCAM180(1)) are key regulators of neuronal development. The extracellular domain of NCAM can occur as a soluble protein in normal brain, and its levels are elevated in neuropsychiatric disorders, such as schizophrenia; however the mechanism of ectodomain release is obscure. Ectodomain shedding of NCAM140, releasing a fragment of 115 kD, was found to be induced in NCAM-transfected L-fibroblasts by the tyrosine phosphatase inhibitor pervanadate, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 108 publications
5
83
0
3
Order By: Relevance
“…In this scenario, the concurrent effects of soluble NCAM and cell contact-dependent interactions after polySia removal would predict that loss of polySia increases cell surface NCAM by inhibition of shedding. There is, however, no reason to assume that NCAM shedding is facilitated by the presence of polySia and all data so far indicate that shed NCAM fragments are not polysialylated (Diestel et al, 2005;Hübschmann et al, 2005;Hinkle et al, 2006;Kalus et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, the concurrent effects of soluble NCAM and cell contact-dependent interactions after polySia removal would predict that loss of polySia increases cell surface NCAM by inhibition of shedding. There is, however, no reason to assume that NCAM shedding is facilitated by the presence of polySia and all data so far indicate that shed NCAM fragments are not polysialylated (Diestel et al, 2005;Hübschmann et al, 2005;Hinkle et al, 2006;Kalus et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that several metalloproteases, such as MMP-2 and MMP-9, as well as the ADAM family of metalloproteases, target NCAM (Brennaman et al, 2014;Hinkle et al, 2006;Hübschmann et al, 2005;Shichi et al, 2011). It has also been shown that inhibition of MMP-2 and MMP-9 prevents NCAM shedding, indicating the roles of these MMPs in NCAM cleavage (Hübschmann et al, 2005;Shichi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it seemed unlikely that PREP itself is able to degrade NCAM. It has been demonstrated previously that NCAM molecule degradation might be mediated by the matrix metalloproteases (MMPs) (Brennaman et al, 2014;Hinkle et al, 2006;Hübschmann et al, 2005;Shichi et al, 2011). Therefore, to test whether increased expression and activity of PREP might be involved in the activation of MMPs, we measured the expression levels and activity of MMP-9.…”
Section: Impaired Differentiation Of Prep-overexpressing Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…in vitro studies have shown that ADAM8 can process several molecules including CD40, tumor necrosis factor-a, IL1R and the immunoglobulin E receptor CD23 (Fourie et al, 2003). Only the CHL1 neural-cell adhesion homolog (Naus et al, 2004), NCAM-140 (Hinkle et al, 2006) and L-selectin (Gomez-Gaviro et al, 2007) have been shown to be processed by ADAM8 in vivo. Whether these or other unknown adhesion molecules can be targeted by ADAM8 during invasion remains to be addressed.…”
Section: Discussionmentioning
confidence: 99%